2017
DOI: 10.1098/rsob.170099
|View full text |Cite
|
Sign up to set email alerts
|

The Ndc80 complex targets Bod1 to human mitotic kinetochores

Abstract: Regulation of protein phosphatase activity by endogenous protein inhibitors is an important mechanism to control protein phosphorylation in cells. We recently identified Biorientation defective 1 (Bod1) as a small protein inhibitor of protein phosphatase 2A containing the B56 regulatory subunit (PP2A-B56). This phosphatase controls the amount of phosphorylation of several kinetochore proteins and thus the establishment of load-bearing chromosome-spindle attachments in time for accurate separation of sister chr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
(140 reference statements)
3
9
0
Order By: Relevance
“…Auroramediated phosphorylation decreases the affinity of Ndc80 for microtubules (Cheeseman et al, 2006), thereby allowing for correction of aberrant kinetochore-microtubule interactions. Consistent with this, Ndc80 phosphorylation is highest in prometaphase and decreases in metaphase through the combined actions of two phosphatases, PP1 and the PP2A-B56 holoenzyme (Liu et al, 2010;Posch et al, 2010;Schleicher et al, 2017). However, recent work has also suggested that a subset of phosphorylation sites are maintained by Aurora A throughout mitosis to ensure proper microtubule dynamics (DeLuca et al, 2017).…”
Section: Core Kinetochore-microtubule Interactionsmentioning
confidence: 71%
“…Auroramediated phosphorylation decreases the affinity of Ndc80 for microtubules (Cheeseman et al, 2006), thereby allowing for correction of aberrant kinetochore-microtubule interactions. Consistent with this, Ndc80 phosphorylation is highest in prometaphase and decreases in metaphase through the combined actions of two phosphatases, PP1 and the PP2A-B56 holoenzyme (Liu et al, 2010;Posch et al, 2010;Schleicher et al, 2017). However, recent work has also suggested that a subset of phosphorylation sites are maintained by Aurora A throughout mitosis to ensure proper microtubule dynamics (DeLuca et al, 2017).…”
Section: Core Kinetochore-microtubule Interactionsmentioning
confidence: 71%
“…At least one protein that is thought to regulate PP2A-B56 activity at kinetochores is Bod1. Bod1 localizes to Ndc80 and is able to inhibit BubR1-bound PP2A-B56 (Porter et al, 2013 ; Schleicher et al, 2017 ) (arrow 25, Figure 1 ). PP1-Knl1 activity may also be modulated by various accessory proteins (Posch et al, 2010 ; Eiteneuer et al, 2014 ; Duan et al, 2016 ), however, this regulation is omitted from Figure 1 , because it is thought to occur in the cytoplasm and not at kinetochores.…”
Section: The Spindle Assembly Checkpointmentioning
confidence: 99%
“…Therefore, Cdk1 jointly stimulates both mitotic arrest and mitotic exit, but it hands the control over to microtubules, which can determine whether kinase or phosphatase activities predominate at the kinetochore (as discussed in detail later). Part of this balance may also be controlled by Bod1, which binds to NDC80 and is phosphorylated by Cdk1 to inhibit PP2A-B56 (Porter et al, 2013 ; Schleicher et al, 2017 ; Figure 2A ). It will be interesting to determine whether microtubule attachment or tension can modulate Bod1 localisation or phosphorylation.…”
Section: The Role Of Cdk1 In Regulating Kinetochore-microtubule Attacmentioning
confidence: 99%
“…BOD1 (Biorientation of chromosomes in cell division 1) is required for chromosomes biorientation during cell division 16 . It is localized at kinetochores from prometaphase until anaphase 16 where it inhibits the phosphatase 2A, thus regulating cell cycle progression 17,18 . A homozygous nonsense mutation in BOD1 (NM_138369: c.334C>T; p.R112*) was previously observed in four female siblings of a consanguineous Iranian family, suffering from mild to moderate ID.…”
Section: Discussionmentioning
confidence: 99%